Cross-cultural adaptation and psychometric assessment of the statement format Decisional Conflict Scale for Mandarin version - Cui Lu; Wei Mu; Ying-hui Jin; Yue-xian Shi; Ge Li; Yan Li; Fei Han; Tian Xia (BMC, 2019)
Abstract Background The statement format of the Decisional Conflict Scale (sf-DCS) is designed and widely used to assess patients' state of uncertainty during health related decision making. As yet no Mandarin version of the sf-DCS has been produced. This study aims to produce the first Mandarin version of the sf-DCS and test its validity and reliability in mainland China. Methods The translation and cross-cultural adaptation of the original English version of the sf-DCS into Mandarin was carried out in accordance with previously published guidelines. The psychometric properties of sf-DCS were assessed in two hypothesized decision-making contexts through online surveys. Results In the online survey designed to test scale validity and reliability, 437 people responded to the influenza immunization survey and 238 responded to the breast cancer screening survey. The results confirm that the Mandarin version of sf-DCS has good criteria validity and the exploratory factor analysis suggested a fitted revised five factors model by removing three items. Respondents who were "unsure" about their decisions/intentions, had read less information, and reported lower self-perceived prior knowledge level scored higher on sf-DCS. The Cronbach's alpha for the sf-DCS total score was 0.963 and that for each subscale ranged from 0.784 to 0.937 in both decision making contexts, and the test-retest correlation coefficient was 0.528. Conclusions The Mandarin version of sf-DCS has good criteria validity and its internal consistency is satisfactory. Our analysis suggests a refinement of the original sf-DCS's factor structure is needed.